2020
DOI: 10.3390/nu12020421
|View full text |Cite
|
Sign up to set email alerts
|

Role of Daily Milk Volume and Period of Lactation in Nutrient Content of Human Milk: Results from a Prospective Study

Abstract: Most studies assessing the macronutrient content of human milk are published retrospectively using analyzers that fail to determine sodium content and do not take into account the role of volume in milk composition. We aimed to describe macronutrient content and sodium content in human milk over time, observe any associations between them, and determine the factors associated with the evolution of milk composition. A prospective, longitudinal, monocentric study was undertaken. Contents of protein, fat, and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
7
1
1
Order By: Relevance
“…Our study revealed that some factors from the mothers and delivery are related to the concentrations of milk proteins. Previous studies suggested that maternal age is an impact factor of HM components and that an older age might be related to lower protein concentrations in some populations [ 36 , 53 ]. The present study observed that women aged 30 years and above had a relatively lower concentration of total protein in the colostrum but a higher concentration in mature milk.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that some factors from the mothers and delivery are related to the concentrations of milk proteins. Previous studies suggested that maternal age is an impact factor of HM components and that an older age might be related to lower protein concentrations in some populations [ 36 , 53 ]. The present study observed that women aged 30 years and above had a relatively lower concentration of total protein in the colostrum but a higher concentration in mature milk.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation was based on the primary outcome of HM processing and not on the secondary outcome parameters of the current study, which might have influenced the results. Although this study enrolled more lactating mothers compared to similar studies [ 9 , 12 , 16 , 18 , 66 , 70 , 71 ], the numbers of underweight and obese mothers were low compared to the group of normal-weight and overweight mothers. Thus, it is important that future studies thoroughly compare the different maternal BMI categories to provide a better insight, especially regarding how underweight and obese lactating mothers differ in their HM compositions compared to normal-weight mothers.…”
Section: Discussionmentioning
confidence: 79%
“…Observed cases show that on day 4, a mother who has given birth prematurely, and undergoing suitable initiation and stimulation of her lactation, supposedly supplies at least 200 ml milk a day collected in six samples minimum per day, namely more than 15 ml of milk per breast in each session of milk collection. From the 7th day, the volume produced is expected to increase to ~400 ml, constituted by a minimum of 30 ml per breast at each collection ( 37 ). However, at the colostral stage, non-contaminated disposable sterile bottles must be preferably used as the collected volumes may be lower: no CS decontamination is necessary ( 38 ).…”
Section: Discussionmentioning
confidence: 99%